The Obligation of Military Institutions to Comply with the Anti-Corruption Act - Fahrizal, Fahrizal S. Siagian; Saied Firouzfar; Najuasah Putra (Faculty of Law, Mulawarman University, 2023)
The purpose of the study is to respond to the corruption crimes committed by military officials in Indonesia, secondly, to explain the obligation of military institutions to comply with the Anti-Corruption Criminal Act, third, to clarify the internal rules of the Military Institutions on Anti-Criminal Corruption in Indonesia. The type of research used is normative law research, which refers to positive law and uses secondary data from primary, secondary, and tertiary law material. Data is collected through Library Research and processed with descriptive analysis. Corruption perpetrated by military officials is a violation of the Military Discipline Act and the Indonesian Criminal Code of corruption. The normative jurisprudential aspect of the fight against corruption in Indonesia is carried out with the advancement of the basis of legal certainty based on the Anti-Corruption Act. According to the legislation, the legal status is generally applicable, and the index of perception of corruption in Indonesia is deteriorating and spreading throughout the line of life of the nation and the country, so that all parties, without exception in military instances, are obliged to comply with the Penalties of Corruption. The entire component of the Indonesian nation must advance the suppression of corruption under the law, including the military instance obliged to voluntarily submit and obey the orders of the Tipikor Rebellion Act. The authorities have drawn up regulations relating to the obligations of the Military Institutions in combating criminal offences of corruption in Indonesia.